1981
DOI: 10.1111/j.1365-2311.1981.tb00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and survival of a seed‐infesting weevil, Pseudanthonomus hamamelidis (Coleoptera: Curculionidae), on its variable‐fruiting host plant, witch‐hazel (Hamamelis virginiana)

Abstract: Abstract. 1. The relative importance of seed abundance and of mortality factors in the population biology of Pseudanthonomus hamamelidis, a hostspecific predispersal seed predator on Hamamelis virginiana, is evaluated by analysis of weevil life tables and abundance estimates in three years with markedly different magnitudes of fruit production. 2. Fruit production of marked Hamamelis individuals averaged 336 m‐2 in 1978, increased three‐ to four‐fold in 1979, and declined again in 1980. More individuals fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…First, the number of seeds consumed will not accurately predict the impact of seed predators on seedling production if additional limitations play a prominent role during germination or seedling emergence. Though contrasting with studies of insect predispersal seed predation (e.g., De Steven 1981, this result is consistent with most studies of postdispersal predation by vertebrates. Second, if predators fail to lower seed densities below the level at which density-dependent seedling mortality operates, predation may affect only the timing of mortality, not the ultimate population size (Harper 1977).…”
Section: Seed Predationsupporting
confidence: 63%
“…First, the number of seeds consumed will not accurately predict the impact of seed predators on seedling production if additional limitations play a prominent role during germination or seedling emergence. Though contrasting with studies of insect predispersal seed predation (e.g., De Steven 1981, this result is consistent with most studies of postdispersal predation by vertebrates. Second, if predators fail to lower seed densities below the level at which density-dependent seedling mortality operates, predation may affect only the timing of mortality, not the ultimate population size (Harper 1977).…”
Section: Seed Predationsupporting
confidence: 63%
“…Adults emerging from hibernation are active from mid-May to early July, and those from the current-year generation emerge from mid-August to early September and then hibernate until the following spring (DeSteven 1981). …”
Section: Resultsmentioning
confidence: 99%
“…Braconid wasps (Hym., Braconidae) and dipteran mainly Tachinidae, cause mortality of acorn weevil larvae when they are exposed for a brief period during burrowing into the soil for pupation or in the prepupal stage if the larvae d o not leave the fruit (BLATCHLEY and LENG 1916;BROOKS and COTTON 1929;CHELLMAN 1954;BREZNER 1960;GIBSON 1969GIBSON , 1982STEVEN 1981). They however, further reported that mortality caused by parasitoids did not affect acorn infestation.…”
Section: Discussionmentioning
confidence: 99%